Influence of teamwork quality, career commitment, and administrator leadership style on innovative behavior of selected teachers in Selangor, Malaysia - Johari, Aduni (2012)
In present globalization challenges, education is set to be one of the transformation tools in generating community who are able to face the insistence of societal demands. This is in line with Malaysia’s mission in achieving world class human capital development. Hence, teachers play a vital role in building the nation’s human capital towards the globalization needs as well as country’s development main mechanism. This scenario leads to the innovativeness inculcated by the teachers in education system. As role models to students, teachers must demonstrate innovative behavior themselves. Therefore, the purpose of this study is to identify the predictors of teachers’ innovative behavior in national secondary schools. The three factors that have predictive potential of teachers’ innovative behavior are teamwork quality,career commitment and administrator’s leadership style. The study also explored the integration of social exchange theory and stage model of innovative behavior as the foundation. The design of this study was a correlational research where a quantitative method was applied on 125 teachers who were selected by random sampling from five schools. The data for this study were collected using a set of questionnaires which scales consists of teamwork quality (Vera & Crossan, 2005), career commitment (Blau, 1988), innovative behavior (Janssen, 2000) and simplified MLQ (Avolio & Bass, 2004). Both descriptive and inferential statistics were applied for data analyses. Data on distribution of respondents based on gender, age, academic qualification and levels of teamwork quality;career commitment; and innovative behavior were analyzed from the descriptive statistics. Pearson product-moment correlation coefficient was conducted to determine relationships between the variables and Multiple Linear Regression by enter method was conducted to predict value of teachers’innovative behavior based on value of teamwork quality, career commitment and administrator’s leadership style as well as to find the dominant factor among the three predictors. The findings of this study revealed that the levels of teamwork quality and career commitment was high but was moderate for innovative behavior among the teachers in schools. In identifying the administrator’s leadership styles in schools, the findings pointed out that transformational leadership style was highly rated followed by transactional leadership style and Laissez-faire leadership style practiced in schools. All three predictors were found to have significant positive relationships with teachers’ innovative behavior with coefficients for teamwork quality, administrator’s leadership style and career commitment by .50, .48 and .23 respectively. Teamwork quality and administrator’s leadership style had moderate relationship while career commitment had low relationship with teachers’ innovative behavior. The findings also designated teamwork quality as the unique contribution (beta =.39) towards teachers’ innovative behavior, compared to career commitment (beta = .01) and administrator’s transformational leadership style (beta = .18)and administrator’s transactional leadership style (beta = .10).Consequently, these results proved that teamwork quality, administrator’s leadership style and career commitment among teachers are significantly related to the selected teacher’s innovative behavior. Thus, the administration and management in the selected teachers’ schools should focus more on these three aspects which could drive towards their innovative behavior.